(3HfGA GbJUGOjGJ GdeYQaI (B:s (3GSJQGJjLjGJ JfehjI eJbOeI (B/s - (3CHh Wg, ehSis; (3eNjeQ, eMeO Gejfs ((3GdYjf(B: s (3OGQ GdcfGH GdLGeYj(B, s, 2009)
(3GJLGgGJ h bVGjG YGdejI fMh GbJUGOjGJ GdeYQaI , GdGWGQ GdJMdjd h YfGUQ GdJejR aj GbJUGO GdeYQaI , YedjGJ HfGA GbJUGO eYQaj , JMSjf GdefXheI GdGbJUGOjI h GdeDSSjI , JYRjR GdGHJcGQ h GdHfjI GdJMJjI ddHMK h GdJcfhdhLjG , JYRjR GdHfjI GdJMJjI dbWGY GdeYdheGJ h GdGJUGdGJ , GdEQJbGA HGdJYdje GdCSGSSj , GdKGdKj h GdJYde eOi GdMjGI , GdJhLjgGJ GdGSJQGJjLjI dYOOef GdOhd h GdJcJdGJ eKd GdUjf h GdgfOs
(3eQGLY U(B.333 (3;edGMb U(B.311s
Keywords: (3GdGbJUGOs; (3GdeYQaIs